Challenges of Application of Cataloguing Standards on Retrieval of Electronic Information Resources in University Libraries in South East Nigeria - Ezema, Anezi Leonard; Ogbuabor, Chimezie Damian; Kanu, Chidi A. (Communicate: Journal of Library and Information Science, 2025)
This study investigated the challenges faced by university libraries in South East Nigeria in applying cataloguing standards to the retrieval of electronic information resources. To achieve this, three research questions with two hypotheses were posed. These cover: extent of application of Cataloguing standards on retrieval of electronic information resources, challenges of application of cataloguing standards on retrieval of electronic information resources and determined strategies for enhancing application of cataloguing standards on retrieval of electronic information resources. The research design used for the study is descriptive survey. The study covers ten (10) public university libraries in South East Nigeria. The population comprises 184 professional librarians in the libraries. The instruments for data collection was questionnaire. The data collected were analyzed using mean and standard deviation. The hypotheses were tested at 0.05 level of significance. Findings indicate that inadequate infrastructure, lack of trained personnel, and inconsistent application of standards are major challenges. The researcher recommends: professional training and capacity building for staff to enhance their understanding and application of cataloguing standards, improved infrastructure to support the cataloguing and retrieval of electronic resources, and collaboration with Standards Organizations to ensure adherence to globally recognized cataloguing standards among other.